Identifying Physic Concepts in Yarn Production by None Fortress Society, Tetaf Village - Demeryati Langtang; Kostan D.F Mataubenu (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
Science learning is better related to nature through local wisdom since learners can gain more comprehension due to familiarity of occurring events through local wisdom based learning and they can preserve the local wisdom. This research aimed to identify physic concepts that occurred in the yarn processing using cotton by local society of None Fortress. The phenomenological design of qualitative research was undertaken in which the data triangulation technique comprised interviews, observation and documentation using an interview sheet, observation sheet and camera as instruments. The identification result of physic concepts in yarn production by None Fortress people covered Energy, Friction, Rotatory Motion, Circular Motion, Simple machine (Gear), Materials elasticity, vibration, measurement, capillarity, and radiation heat transfer. Based on the invented concepts, further research will expected to integrate the identification result in physic learning.